التبدلات الوبائية والإمراضية لسرطانات الجلد اللاميلانية في السنوات الأخيرة - بدور رولا (Latakia University Journal -Medical Sciences Series, 2013)
سرطانات الجلد اللاميلانية هي الخباثات الأكثر شيوعا. وتضم السرطانة قاعدية الخلايا و السرطانة شائكة الخلايا. تهدف الدراسة إلى تحديد التبدلات المحتملة, السريرية والإمراضية المرافقة لهذه الآفات خلال السنوات الأخيرة وتقييمها. دُرست وحلّلت قائمة مؤرشفة لحالات سرطانات الجلد اللاميلانية المشخصة خلال الأعوام (1998-1999-2000) والأعوام (2009-2010-2011) في إحدى المشافي الجامعية الكبرى في اللاذقية )مشفى الأسد الجامعي). تضمنت الإمراضية المشاركة المدروسة: النمط النسيجي للورم قاعدي الخلايا (العقيدي,السطحي, والمرتشح) وكذلك الدرجة النسيجية للورم شائك الخلايا(جيد,متوسط, وسيْ التمايز), أما العوامل الديموغرافية فشملت العمر, الجنس, والتوضع. النتائج: كان السرطان قاعدي الخلايا هو النمط المسيطر خلال فترتي الدراسة. النسبة قاعدي \شائك كانت أعلى من تلك المسجلة منذ 9 سنوات. التوضع الأشيع كان الرأس و العنق. غالبية الحالات شخصت بين 60-80 سنة. حصل كل من النمط العقيدي للورم القاعدي و النمط جيد التمايز للورم الشائك على نسب الحدوث الأعلى, لكن هذه النسب تبدلت مع الوقت ليبقى في المقدمة النمط العقيدي بانخفاض طفيف ((P=0.31 يتبعه مع ارتفاع بسيط النمط السطحي (P=0.11 )، و من ثم المرتشح (P=0.28), أما النمط جيد التمايز للSCC فبقي في المرتبة الأولى مع تسجيل ارتفاع هام بالمقابل للنمط متوسط التمايز في الوقت الحالي (P=0.009). معظم مرضى العينة كانوا ذكورا باستثناء حالات SCC للسنوات الأخيرة حيث تفوقت الإناث. Nonmelanoma skin cancer (NMSC) is the most common diagnosed malignancy. The NMSC consists of basal cell carcinoma (BCC) and squamous cell carcinoma (SCC). The purpose is to determine and evaluate the potential clinical or pathological changes of these lesions in the last years. A group of archived cases of (NMSC) diagnosed in (1998-1999-2000) and in (2009-2010-2011) at a large university hospital in Lattakia (Alassad university hospital) was studied. The studied pathologic attributes included the histological type of BCC (nodular, superficial, infiltrating) and histological grade of SCC ( well, moderate, and poorly differentiated). Demographic features included age, sex and location. The results are: Basal cell carcinoma was the predominant form of NMSC over the two study periods. BCC/SCC rate was higher than that reported before 9 years. The most common location is the head and neck. Most cases were diagnosed among patients aged (60-80) years. Both the nodular type of BCC and the well differentiated SCC had the higher rates. These rates have changed in time but the nodular BCC remained the most common type with slight decrease (P=0.31) followed by superficial (P=0.11) and then infiltrating (P=0.28). As for the well differentiated SCC, it remained the first with a significant increase in moderately differentiated SCC (P=0.009). The majority of patients were males except for the last years; the majority of SCC cases were females.